Determinación de la composición química del aceite esencial de Thymus vulgaris L. "Tomillo", determinada por cromatografía de fase gaseosa, espectrometría de masa GCIMS y análisis de su actividad antimicrobiana - Acosta, Olinda (2000)
A study of the essential oil extracted from the leaves and flowers of the Thymus vulgris L. ''Tomillo'' by stearn distillation method was carried out. Samples were determined by physico-chemical analyses and chemical composition was obtained by GC/MS mass spectrophotometer coupled to gaschromatographer, determining the following hydrocarbonated compounds like: Thujene; 1,3,6 Octatriene,3,7-Dimethyl; Camphene; Beta Myrcene; Delta 4 Carena; Beta Selinene; Delta Cadinene; Benzene 1 methyl, 4 (l-methyl ethyl); Gama Terpinene; Trans Caryophyllene; Germacrene D.; Trans Caryophyllene; Beta Bisabolene y compuesto oxigenados como: 7 octen, 401 (CAS); l.6 octadien, 3 0l, 3,7 Dimethyl Acetate; Linalool; Isoborneol; carvacrol; Thymol; Farnesyl acetate 2.At the same time, antimicrobial activity was determined against pathogenic strains from clinical samples and from ATCC (American Typical Cultivate Collection) strains, observing inhibitory activity against the following strains: Escherichia coli, Escherichia coli, ATCC 25922 Micrococcus luteus ATCC 9341, Staphylococcus aureus ATCC 6538, Streptococcus β hemolítico, Staphylococcus epidermidis N° 36, Shigella flexnery, Salmonella paratyphi, Salmanella typhi, Candida albicans ATCC 10231, Candida albicans, Pseudomonas aeruginosa.